2009
DOI: 10.1164/rccm.200806-975oc
|View full text |Cite
|
Sign up to set email alerts
|

Variable Tidal Volumes Improve Lung Protective Ventilation Strategies in Experimental Lung Injury

Abstract: Noisy ventilation with variable Vt and fixed respiratory frequency improves respiratory function and reduces histological damage compared with standard protective ventilation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
137
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 37 publications
10
137
2
2
Order By: Relevance
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
“…Additionally, the redistribution of pulmonary blood fl ow from cranial to caudal and from ventral to dorsal lung zones was higher and diff use alveolar damage less when variable ventilation was associated with the ventilation strategy recommended by the ARDS Network. Such a redistribution pattern of pulmonary perfusion, which is illustrated in Figure 3, is compatible with lung recruit ment [41].…”
Section: The Role Of Variable Ventilation As a Recruitment Maneuversupporting
confidence: 57%
“…Additionally, the redistribution of pulmonary blood fl ow from cranial to caudal and from ventral to dorsal lung zones was higher and diff use alveolar damage less when variable ventilation was associated with the ventilation strategy recommended by the ARDS Network. Such a redistribution pattern of pulmonary perfusion, which is illustrated in Figure 3, is compatible with lung recruit ment [41].Th e phenomenon of stochastic resonance may explain the higher effi ciency of variable ventilation as a recruitment maneuver. In non-linear systems, like the respiratory system, the amplitude of the output can be modulated by the noise in the input.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…However, the CVRs in Vt and Ti were significantly different between PS and NAVA (p<0.005), with NAVA tidal volumes and inspiratory time more variable. As increased variability has previously been associated with improved ventilation/perfusion ratio and improved oxygenation both in animal models [11][12][13] and humans [14], the ability of NAVA in maintaining higher variability in tidal volume compared to PS could be of potential clinical interest and will require further investigation. Moreover, overall, it is hypothesized that greater variability in breathing pattern is a healthier patient condition.…”
Section: Discussionmentioning
confidence: 99%